Surgical Management of Juxtafacet Cysts - Hosam Habib (Egyptian Spine Association, 2013)
Background Data: Synovial cysts occur most frequently in the lumbar spine (88-99%). They are viewed as regenerative changes that are associated with hypermobility and instability of a motion segment as seen with spondylolisthesis and facet joint instability and facet degeneration. There is extensive controversy regarding the definition, prevalence, pathogenesis, risk factors, and most importantly, treatment options for synovial cysts management. Purpose: To assess the outcome of various surgical procedures done for the treatment of lumbar juxtafacet cysts. Study Design: Retrospective clinical case study. Patients and Methods: The data of 26 patients (17 males and 9 females) who underwent surgery for lumbar juxtafacet cysts, during the years 2005 to 2010 was reviewed. The patients age ranged from 42 to 68 years (mean 55.9 years ± 6). The most affected level was L4–L5 (21 patients), followed by L3–L4 (3 patients), while the least affected level proved to be L5-S1 (2 patients). Five patients had in addition, spondylolisthesis of the involved segment and four patients had hypermobile segments. All patients had signs of nerve root compression that failed to respond to conservative treatment preoperatively. Various patients groups were subject of alternative surgical modalities; as Microscopic laminotomies and medial facetectomies were performed in 5 patients (laminotomy group), formal Laminectomies and medial facetectomy in 12 patients (laminectomy group), while complete facetectomy with additional fusion for spondylolisthesis and hypermobility were performed with 9 patients (fusion group). Results: Conservative treatment proved to be ineffective in all cases. The mean follow up duration was for 28 months (± 7.5) ranging from 18 to 46 months. Excellent to good outcome was achieved in 17 of 26 patients (65.4%), while 6 patients (23.1%) showed fair results and 3 (11.5%) showed poor results. Persistent low back pain was not observed at all among patients of the fusion group (0 out of 9 patients); while being more common in patients operated without fusion (laminotomy and laminectomy groups) (7 out of 17 patients). Moreover, three patients of the latter group have developed grade 1 olisthy during the follow-up duration, and hence requiring additional fusion. Conclusion: Juxtafacet cysts can be treated effectively through different surgical modalities, which should be tailored according to the anatomical and dynamic properties of the patients’ spines, as well as their presenting complaints. The presence of radiological instability even in the absence of overt slippage may necessitate the need for fusion. (2013ESJ050)